57 POTENTIALLY INAPPROPRIATE MEDICATION USE AND MORTALITY IN PATIENTS WITH COGNITIVE IMPAIRMENT. (18th November 2021) - Buckley, E; Jonsson, A; Flood, Z; Lavelle, M; Nurdin, N; Dowling, P; Duggan, E; O'Sullivan, N; McGreevy, C; Duggan, J; Kyne, L; McCabe, J
Abstract: Background: Potentially inappropriate medications (PIMs are associated with falls, hospitalisation, and cognitive decline. Few studies have investigated the association between PIMs related to cognitive impairment (PIMCog) and mortality in dementia or mild cognitive impairment (MCI). Methods: This was a retrospective observational study. Patients diagnosed with MCI or dementia (DSM-IV criteria) presenting to a tertiary-referral memory clinic from 2013–2019 were eligible. The primary outcome was all-cause death. Secondary outcomes were vascular death and non-vascular death defined according to formal certification. The primary exposure variable of interest was PIMCog, defined as any medication in the Beers 2015 or STOPP criteria, classified as potentially inappropriate for patients with cognitive impairment. Anticholinergic burden was measured using the anticholinergic cognitive burden (ACB) scale. Polypharmacy was defined as ≥5 medications. Cox proportional hazard models were used to calculate hazard ratios (HRs) and 95% confidence intervals (95% CIs). Results: There were 418 patients included (n = 261 dementia, n = 157 MCI). The median age was 79 (interquartile range IQR 74–82) and median follow-up was 809 days (IQR 552–1, 571). One or more PIMCog was prescribed in 141 patients (33.4%). PIMCog use was associated with all-cause mortality after adjustment for age, sex, dementia severity, Charlson Co-morbidity Index, chronic obstructive pulmonary disease, congestive cardiac failure, and peripheral vascular disease (HR 1.96, 95% CI 1.24–3.09). PIMCog use was associated with vascular death (HR 3.28, 95% CI 1.51–7.11) but not with non-vascular death (HR 1.40 95% CI: 0.78–2.52). Neither an ACB ≥3 (HR 0.87, 95% CI: 0.46–1.64) or polypharmacy (HR 1.87, 95% CI: 0.67–5.24) were associated with death. Conclusion: The burden of PIMCog use in patients with cognitive impairment is high. PIMCog use is independently associated with all-cause mortality and vascular death. This is a potential modifiable risk factor for death in patients with neurocognitive disorders. Further research is required to independently validate this finding.